Two new species of Heteromysis (Olivemysis) (Mysida, Mysidae, Heteromysinae) from the tropical northwest Atlantic with diagnostics on the subgenus Olivemysis Băcescu, 1968 - Price, W. Wayne; Heard, Richard W. (Zootaxa, 2011)
A survey of mysid crustaceans in near-shore habitats of the Cayman Islands and the Turks and Caicos Islands, BWI yielded two new species of mysids belonging to the genus Heteromysis S. I. Smith, 1873. H. (Olivemysis) modlini n. sp. occurred on live bottom habitats in shallow waters of Grand Cayman Island, and H. (Olivemysis) mclellandi n. sp. from sponges in depths of 21–27 m on deep fringing reefs off Pine Cay, Turks and Caicos Islands. H. modlini may be distinguished from closely related species in the western Atlantic by the following characters: (1) 6–7 robust flagellated setae on the medial margin of the carpo-propodus of thoracic endopod 3, (2) 3–5 and 4–6 bent, attenuated spines on male pleopods 3 and 4, respectively, (3) 3–4 spiniform setae along the medial margin of the uropodal endopod, and (4) 10–16 spinules along the anterior ¾ of the telsonic cleft, 14–19 spiniform setae completely lining the lateral margins of the telson, and each apical lobe of the telson with a pair of spiniform setae, the outer 1.6–2.0 times longer than the inner. Heteromysis (Olivemysis) mclellandi is unique among known heteromysids in having modified attenuated setae on pleopods 1– 5 of both males and females, and may be distinguished further from its related Caribbean congeners by the following characters: (1) tuberculate flagellated seta on the antennular peduncle, (2) 8–9 flagellated setae on the carpo-propodus of thoracic endopod 3, and (3) telson cleft depth: telson length ratio of about 1/6, and outer: inner length ratio of apical telson setae of 1.2–1.6. Diagnostic tables separating the two new species from related Caribbean congeners are presented. The subgenus Olivemysis Băcescu, 1968 is diagnosed and discussed; based on a critical review of the literature, 10 species, besides H. (Olivemysis) modlini n. sp. and H. (Olivemysis) mclellandi n. sp., are placed in this subgenus, bringing its total species number to 30.